Dynamics and Trends in Vaccine Procurement and Distribution in Zimbabwe - Maketo, John P; Mutizwa, Bismark (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2021)
The subject of COVID-19 vaccines has generated debate across the globe as it has created a fecund ground for a plethora of dynamics such as vaccine diplomacy, misinformation, and struggle for dominance among global powers to mention but a few. Thus, the vaccine subject has taken-center stage in global discourses, resulting in developing and developed nations experiencing challenges in respect to purchase, transparency, and accountability in the administration of vaccines. The subject of vaccines in Zimbabwe has provoked public skepticism indicative of the existing trust deficit between government and the citizens. This emanates from strong evidence of abuse of public resources and hence questions of transparency and accountability especially in relation to disaster situations. To this end, this paper seeks to bring to light the trends and dynamics in vaccine procurement and distribution in Zimbabwe. The study examines the correlation between vaccine diplomacy (donation-trap diplomacy) and vaccine purchases. A chronological analysis of the approved vaccines, rejection of Johnson and Johnson and sudden acceptance, natural resource implications of the donations from ALROSA, poor public resource management, vaccine shortages, vaccine misinformation and vaccine cheating. Possible ways of enhancing vaccine intake through quality information are also discussed and Zimbabwe`s performance against other African nations is examined. The research ends by proposing a series of questions which should be embraced to fully comprehend the trends and dynamics of vaccine procurement and distribution.